The Effect of Tutorial Instructional Model Based on E- Learning Towards Students’ TIK Subject Matter Achievement in X SMAN 1 East Praya, Central Lombok in Academic Year 2016/ 2017 - Abdurrazak; Mahsur (International Journal of Sociology of Religion, 2023)
The goals of suitable instructional model were for creating the condusive condition in teaching and learning process. With the condusive condition the students would be more active and fun in learning the materials. The conventional method was one of the engender students’ achievement were low. Based on the background, the problem statement here, was there an Effect of Tutorial Instructional Model Based on E-Learning Towards Students’ TIK Subject Matter Achievement in X SMAN 1 East Praya, Central Lombok in Academic Year 2016/ 2017?. While the purposed of this study was for knowing the Effect of Tutorial Instructional Model Based on E-Learning Towards Students’ TIK Subject Matter Achievement in X SMAN 1 East Praya, Central Lombok in Academic Year 2016/ 2017. Further more, this study used Cluster Random Sampling in taking sample. Besides that the collecting data here used tests as a main method while the documentation, observation and interview as acomplement method. Thus for the data analysis used T-test. Based on the data analysis found t-test as a 4,475 and t- table 2,048 in significance level 5% with d.b (N-1)= 29-1= 28. On the other words t-test was bigger than t-table (4,475> 2,048) which means (Ha) was accepted and (Ho) was rejected thus for, there was an Effect of Tutorial Instructional Model Based on E-Learning Towards Students’ TIK Subject Matter Achievement in X SMAN 1 East Praya, Central Lombok in Academic Year 2016/ 2017. Shortly, this study was “significance”.